Deconvolving the saturation state and temperature controls on benthic foraminiferal Li/Ca, based on downcore paired B/Ca measurements and coretop compilation. (1st September 2018) - Doss, Whitney; Marchitto, Thomas M.; Eagle, Robert; Rashid, Harunur; Tripati, Aradhna
Abstract: Li/Ca in calcitic benthic foraminiferal tests has been suggested to co-vary with both temperature and carbonate chemistry, but these two influences have been difficult to disentangle. We use several new downcore records of Li/Ca in Cibicidoides wuellerstorfi and Uvigerina, paired with the carbonate proxy B/Ca, to further elucidate this behavior. We also combine the downcore measurements with a compilation of coretop Li/Ca data. Uvigerina B/Ca presumably records pore water saturation with respect to calcite (ΔCO3 2− ), though downcore data show that it partially reflects bottom water ΔCO3 2− (inferred from C. wuellerstorfi B/Ca), with a relationship that is consistent with a previous global coretop calibration. Downcore Li/Ca is significantly correlated to B/Ca in both taxa, implying a positive relationship between Li/Ca and carbonate chemistry. This connection breaks down in the coretop compilation however, likely due to the confounding influence of temperature on Li/Ca. We attempt to isolate the temperature influence using a negative exponential equation previously derived from abiotic calcite precipitation experiments, and introduce a new quantity ΔLi/Ca, which is the observed departure from the temperature-based prediction. This transformation brings the downcore and coretop Li/Ca measurements into alignment, with up to 90% of the ΔLi/Ca variance explained by ΔCO3 2− . Finally, we perform preliminary tests of Li/Ca as a paleo-proxy for both ΔCO3 2− and temperature.